(untitled) (Research, Society and Development, 2022)
There are some articles that concern of hearing of children with microcephaly carried by Zika Virus, but it was no notice of the manifestations and integration of auditory and linguistic skills. Purpose: To analyze and compare the results of the Brainstem Evoked Response Audiometry (BERA) with the application´s results of the Early Language Milestone Scale (ELM) in children with microcephaly by congenital infection by the Zika Virus. Methodology: This is a cross-sectional, retrospective study and the study of case carried out from the analysis of nine medical charts of children attended at speech therapy. It was included the charts with complete information of head circumference at birth, BERA and ELM evaluation. Results: The BERA analysis pointed the absence of retrocochlear alterations despite of the integrity of the auditory pathways, the language skills that support the linguistic development were compromised according to the ELM results. Conclusion: The abnormal linguistic development of children with microcephaly by Zika virus was not associated with auditory development and maturation, which may indicate a possible lesion of superior cortical structures of the brainstem, which was not evaluated by the BERA.